Sensitivity improvement in the measurement of minor components by spatial confinement in fiber-optic laser-induced breakdown spectroscopy - Qiu, Yan; Shi, Mingxin; Guo, Xinyu; Li, Jinghui; Wu, Jian; Zhou, Ying; Sun, Hao; Hang, Yuhua; Li, Xingwen; Li, Yongdong (Spectrochimica acta. Part B: Atomic spectroscopy, 2023)
Nuclear power overhaul can benefit from a fiber-optic laser-induced breakdown spectroscopy (FO-LIBS) setup for in situ composition measurements. Regarding FO-LIBS, the pulsed energy of the fiber-delivery laser is limited, and the spot profile received by the sample surface is distorted from a Gaussian to a flat-top distribution. Therefore, the induced plasma in FO-LIBS is characterized by weakened emission, shortened lifetime, and insufficient sampling of minor components compared with that of conventional LIBS. This could not meet the quantitative demands of the minor component with a concentration of 0.01 wt% or lower in structural steel. In this study, by modifying the mechanical structure of the front-end sensor, a space constraint condition can be created for plasma emission enhancement. By combining the optical diagnostics of fast photograph and shadowgraph, shockwave propagation and plasma expansion can be visualized synchronously. The reflected shockwave decelerates in the process of propagating towards the plasma, accompanied by morphological changes from the oblate cylinder to the hemisphere. It can be demonstrated that the plasma is constricted by the reflected shockwave associated with a significant increase in the plasma temperature and electron number density. The plate spacing determines the time delay of spectral enhancement and also determines the enhancement factor corresponding to the velocity attenuation of shockwave propagation over a long distance. The enhancement factor is found to be inversely proportional to the quadratic square of the propagation velocity of shockwave just after reflection, and shows an upward trend with increasing upper-level energy of atomic transitions. A maximum enhancement factor of ∼3.52 is realized with a time delay of 4 μs at a plate spacing of 3 mm, and trace components Mo, V, and Cu are newly recognized, which cannot be observed in conventional FO-LIBS. Meanwhile, the calibration of trace Cr and Mn suggests that the quantitative results using the sensor coupled with spatial confinement are comparable, and the limits of detection are reduced to 31 ppm and 475 ppm, respectively. [Display omitted] •Spatial confinement is firstly introduced into FO-LIBS for sensitivity improvement.•A portable FO-LIBS sensor with parallel plates is developed to restrict plasmas.•The change of plasma morphology and shockwave propagation is synchronously visual.•The spectral enhancement is in a negative quadratic correlation with plate spacing.•The method of spatial confinement promotes applicability of FO-LIBS in nuclear power.